Holographic entanglement negativity for conformal field theories with a conserved charge - Parul Jain; Vinay Malvimat; Sayid Mondal; Gautam Sengupta (European Physical Journal C: Particles and Fields, 2018)
Abstract We study the application of our recent holographic entanglement negativity conjecture for mixed states of adjacent subsystems in conformal field theories with a conserved charge. In this context we obtain the holographic entanglement negativity for zero and finite temperature mixed state configurations in d-dimensional conformal field theories dual to bulk extremal and non extremal charged $$AdS_{d+1}$$ AdSd+1 black holes. Our results conform to quantum information theory expectations and constitute significant consistency checks for our conjecture.